CD161 Expression on Mucosa-Associated Invariant T Cells is Reduced in HIV-Infected Subjects Undergoing Antiretroviral Therapy Who Do Not Recover CD4+ T Cells - Michael L Freeman; Stephen R. Morris; Michael M. Lederman (Case Western Reserve University, 2017)
Background: Mucosa-associated invariant T (MAIT) cells are a recently identified class of innate-like T cells that are involved in the mucosal immune response. MAIT cells are characterized by expression of TCR Va7.2 and CD161. In HIV infection, there is a profound early loss of MAIT cells from the circulation that never fully recovers, even after prolonged viral control with antiretroviral therapy (ART). Methods: We analyzed PBMCs from fresh whole blood from HIV-negative or ART-treated HIV-positive donors with full (Immune Success) or impaired (Immune Failure) CD4+ T- cell recovery by flow cytometry for T-cell markers, TCR Va7.2, and CD161. The PBMCs were cultured with or without TCR-mediated stimulation, and CD161 expression was assessed on Va7.2+ T cells. Interferon-g (IFNg) production was assessed by intracellular cytokine staining. Results: We found a decrease in the percentage of CD3+ T cells that expressed CD161 and the percentage of Va7.2+ T cells that expressed CD161, in HIV-infected individuals. We also found a significant increase in the percentage of T cells that were Va7.2+CD161- in immune failure compared to controls, accompanied by an increase in the percentage of Va7.2+CD161- T cells that express CD8+ in donors with immune failure, but not immune success. After TCR stimulation in vitro, Va7.2+ T cells reduced expression of CD161, yet Va7.2+ CD161- cells from immune failure donors retained the ability to express IFNg on stimulation. Conclusions: Our findings suggest that in immune failure patients, the reduction in peripheral MAIT cells is due, at least in part, to a loss in CD161 expression, and is not merely the result of trafficking into mucosal tissues or cell death. These CD161- cells retain their function.